EVALUATION OF THE IMPLEMENTATION OF THE CIPP MODEL CHARACTER EDUCATION STRENGTHENING PROGRAM (CONTEX, INPUT, PROCESS, PRODUCT) - Erna Krisnawati (International Journal of Teaching and Learning, 2024)
The Character Education Strengthening Program (PPK) is an educational program in schools to strengthen students' character through harmonization of heart, feeling, thought and sports with the support of public involvement and cooperation between schools, families and communities which is part of the National Movement Mental Revolution (GNRM. The aim of the research is to evaluate the Character Education Strengthening Program by taking samples at SD Muhammadiyah Pacul, Tegal Regency. This research method is evaluative descriptive research which aims to provide an overview of the scope of the program to be evaluated. For this reason, the data analysis technique used is descriptive analysis using the CIPP (Contex, Input, Process, Product) Model. The population in this study was the academic community and students of SD Muhammadiyah Pacul. The sample in this study included school principals, teachers and staff as well as grade 5 students. The determination of the student sample was based on the theory of child psychological maturity. The results of the research show that the implementation of the character education strengthening program at SD Muhammadiyah Pacul in terms of context, input, process, product, is quite effective at SD Muhammadiyah Pacul. BecauseThis program material is relevant to school needs. Judging from the school's strategic plan.The obstacles that exist are more external factors such as school culture related to the role of parents in children's education at school and internal factors related to teachers' mastery of information technology skills, especially teachers who are no longer young.